How social innovations can enable socially just spatial politics and collaborative professionalism in music education : The case of AÏCO at the Conservatoire de Lyon - Galmiche, Martin; Westerlund, Heidi; Laes, Tuulikki; Väkevä, Lauri (Routledge, 2024)
This chapter presents AÏCO (Instrument Learning and Collective Invention), a programme for social justice that emerged from the collaboration between the Conservatoire de Lyon and a primary school in an underprivileged area within the Lyon metropolitan area. The programme aims to make instrumental tuition more accessible for children living in this particular area and involves musiciens intervenants specialised in creating collaborative and institutional interfaces for music learning. The musicians collaborate with the primary school teachers (during school hours) but also with the instrument teachers at the Conservatoire (outside school hours). This bridging of institutional practices creates, by transitivity, a connection between the Conservatoire and the primary school and consequently with the children and their families living in the surrounding area. The authors argue that by conceiving social innovations such as AÏCO, conservatories can present themselves to society as physical, imagined, and lived spaces that provide room for thinking, planning, and realising more equal educational possibilities and expanded social justice. The practical conclusion is that owing to their special position in society and music education systems, musiciens intervenants can play a crucial role in both the spatial politics and the pedagogical choices of conservatories when given the possibility to imagine new collaborations.
Keywords: musiikki; musiikkioppilaitokset; musiikkikasvatus; Ranska; musiikkikorkeakoulut